Electric dipole moments in the minimal scotogenic model - Asmaa Abada (Journal of High Energy Physics, 2018)
Abstract In this work we consider a minimal version of the scotogenic model capable of accounting for an electron electric dipole moment within experimental sensitivity reach in addition to providing a dark matter candidate and radiatively generating neutrino masses. The Standard Model is minimally extended by two sterile fermions and one inert scalar doublet, both having odd parity, while the Standard Model particles have an even parity, imposed by a ℤ2 symmetry. The neutrino Yukawa couplings provide additional sources of CP violation, and thus a possible impact on electric dipole moments of charged leptons. This model provides two possible dark matter candidates (one bosonic and one fermionic) and our results show that, independently of the ordering of the generated light neutrino spectrum, one can have sizeable electron electric dipole moment within ACME sensitivity reach in the case of fermionic dark matter candidate.